Association between preoperative serum albumin level and postoperative wound complications in emergency laparotomy - Pant, Sudip; Aryal, Rishi Kant; Thapa, Nirmal (Journal of Karnali Academy of Health Sciences, 2026)
Introduction: Serum albumin level is a standard, readily available parameter that predicts preoperative mortality and morbidity. Levels above 3.5 g/dL indicate sufficient protein reserves to support biological processes. Patients with levels below 3.2 g/dL are more likely to have poor outcomes.Methods: This was a cross-sectional study from April to October 2023 at Bir Hospital’s Department of General Surgery, using convenience sampling of patients undergoing emergency laparotomy. Eligible participants were adults 20+ who consented. Exclusions included icterus, hemoglobin